I have the following expression -

(5+4/3)x-(10/3)=-16

x=-2

Can someone please show me the steps to x=-2 as I am not getting this when checking my workings.

Thanks

Printable View

- May 25th 2013, 08:51 AMmrmorrisonBasic Algebra - Solving the expression
I have the following expression -

(5+4/3)x-(10/3)=-16

x=-2

Can someone please show me the steps to x=-2 as I am not getting this when checking my workings.

Thanks - May 25th 2013, 09:04 AMdokrbbRe: Basic Algebra - Solving the expression
Hi there,

(5+4/3)x-(10/3)=-16

(5+4/3)x=-16+(10/3)

(19/3)x=-(38/3)

x=-(38/3)/(19/3)

x = -114/57

x=-2, here it is - May 25th 2013, 09:17 AMmrmorrisonRe: Basic Algebra - Solving the expression
Thanks - I can see where I was going wrong.

-16 needs to be multiplied by 3 in order to have a common denominator with 10/3.